Determination of individual glucose threshold using pharmacy portable blood glucose meter - de Sousa, Nuno Manuel Frade (2019)
Introduction: The individual glucose threshold (IGT) has been used to estimate the anaerobic threshold with low-cost analyses and shorter times. However, the reliability of the glycemic analysis using a portable pharmacy glucose meter has received little attention. Objective: To identify the IGT using a portable glucose meter and to compare it with the ventilatory threshold (VT). Methods: Fourteen active, healthy men (25.9 ± 3.2 years; %BF = 17.9 ± 3.7%) performed an incremental treadmill test. The anaerobic threshold was identified by two different methods: (1) IGT, corresponding to the intensity of the lowest glucose value during the test; and (2) VT, corresponding to the break in linearity of the ventilation curve and an increase in the respiratory oxygen equivalent, without an equivalent increase in carbon dioxide. Results: There were significant differences between VT (9.9 ± 1.2 km/h) and IGT (9.5 ± 1/1 km/h), corresponding to 75.4 ± 9.2 and 72.5 ± 10.4 %VO2max, respectively. The methods presented high correlation (r = 0.82, p = 0.002) and the Bland-Altman technique showed agreement between IGT and VT, with a mean difference of 0.5 km/h. Conclusion: It was possible to determine the intensity of IGT by the glycemic response in the incremental test using a portable glucose meter. The IGT underestimated the intensity of VT by approximately 0.5 km/h, but with a high correlation and agreement between them. Level of evidence III, Case-Controle Study.